Case Management Models and Continuing Care: A Literature Review across nations, settings, approaches, and assessments. Issue 2 (May 2021) - Yu, Ziwa; Gallant, Allyson J.; Cassidy, Christine E.; Boulos, Leah; Macdonald, Marilyn; Stevens, Susan
Older adults accessing continuing care often have multiple chronic conditions. Research suggests that case management is a promising approach to reduce health care expenditure and improve patient outcomes. To optimize healthcare delivery, an examination of existing case management models and their effectiveness is essential. This literature review was conducted using Joanna Briggs Institute (JBI) methods to explore case management models for older adults accessing continuing care services. Searches were conducted in PubMed and CINAHL from 2010 to 2018. A total of 37 articles were included in this review. Approaches to case management are diverse with respect to composition of care providers, method of care provision, and location of care. Findings from 27 quantitative studies demonstrated that nurse-led and interdisciplinary team case management models that include home visits can effectively reduce hospital admission/readmission while lowering costs. Mixed results were found on the impact of case management on patient satisfaction, ED visits, quality of life, length of stay, self-efficacy, social integration and caregiver burden. Among 10 qualitative studies, 3 facilitators for quality case management were identified that include receiving care at home, building trusting relationships, and improving self-efficacy. Based on these findings, we conclude that nurse-led and interdisciplinary team case management can effectively reduce hospital admission of frail older adults while lowering costs, particularly within home care settings.